The use of heart rate variability analysis to detect arrhythmias in horses undergoing a standard treadmill exercise test - Ladina Frick; Colin C. Schwarzwald; Katharyn J. Mitchell (Journal of Veterinary Internal Medicine, 2019)
Background Little is known about normal heart rate variability (HRV) in horses during exercise. It can be difficult to separate premature beats from normal beat‐to‐beat variation at higher heart rates. Objectives The aim was to quantify HRV in healthy horses during a high‐speed treadmill‐standardized exercise test (HSET) and to compare with the HRV in horses observed to have arrhythmias during exercise. Animals Thirteen healthy horses (Group H), 30 horses with arrhythmias (Group A), and 11 horses with poor performance but no observed arrhythmias (Group O). Methods Prospective, observational study. All horses performed a HSET with simultaneous electrocardiograph (ECG) recorded. The ECGs were corrected for artifacts, and arrhythmias noted. Percent instantaneous beat‐to‐beat cycle length variation (% R‐R variation) was calculated, and HRV analyses were performed on trot, canter, and recovery segments. Results Group H showed between −4.4 and +3.8% R‐R variation during trot and between −6.1 and +5.4% R‐R variation during the canter phase of the HSET. Group A had significantly larger maximum and 1st percentile R‐R shortening and lengthening compared with Group H and Group O during the recovery phase where most arrhythmias were observed. During recovery, a cutoff of 6% maximum % R‐R shortening predicted the presence of arrhythmia with 88% sensitivity and 97% specificity and likelihood ratio of 26. Conclusions and Clinical Importance Healthy horses have little instantaneous R‐R variation during exercise. If a cardiac cycle shortens more than 6% from the previous cycle during the recovery phase, this R‐R interval is likely to represent an arrhythmic event.